Electronic Portfolios for Developing Reflective Practice in Educational Leaders - Dixon, Robert (Australian Association for Research in Education, 2011)
The aim of this paper was to investigate how an electronic portfolio could promote reflective practice, professionalism and accountability in educational leaders in West Australian schools. Participants were trained in the navigation of a portfolio software application engineered by the author, then provided with skills in the various technical aspects required to use it effectively. The software was designed to encourage self analysis through reflective practice using the Wildy and Louden (2002) Leadership framework as the conceptual model for the study. Eighteen key qualities and attributes were identified by the group as crucial concerns of their leadership approach; values, the quality of the relationship they had with their staff, the school as a physical and cultural entity, curriculum, communication, students, parents and community, pedagogy, leadership, management process and policy as well as the resourcing of ICT infrastructure were important concerns. Change and change management permeated thinking. The findings also suggested a general perception by participants, that a positive attitude in the discharge of leadership responsibilities as educational leaders was a very important attribute which fostered an ability to create a collaborative and cooperative environment in which things could get done. The study has demonstrated that a carefully constructed portfolio based on a solid conceptual model can promote reflective practice which can develop critical consciousness and perspective transformation in school leaders.